Effect of organic acids and NaCl on the rheological properties of dough prepared using Pembina and Harvest CWRS wheat cultivars. Issue 3 (16th April 2018) - Stone, Andrea K.; Lam, Ricky S. H.; Hopkins, Erin J.; Hucl, Pierre; Scanlon, Martin G.; Nickerson, Michael T.
Abstract : Background and objectives: The effect of organic acids (1.2 mmol/100 g flour: acetic, citric, lactic or fumaric acid) and NaCl content (0%, 1% and 2%, flour weight basis) on the rheological properties and stickiness of dough prepared using two CWRS wheat cultivars (Harvest and Pembina) was investigated as a means of understanding the interaction of salt and acid on dough viscoelastic behavior. Findings: Overall higher salt levels made the doughs stiffer and less sticky as evident by |G*| and J el increasing and dough stickiness decreasing as salt content increased. The addition of citric, acetic, and lactic acids caused an overall increase in |G*| and J el, and a decrease in tan δ and J max, whereas fumaric acid had the inverse effect. Dough stickiness increased regardless of the type of acid added at all salt levels but more so when no salt was added to the dough. The effect of acid addition on dough rheology was cultivar dependent as evident by a small overall increase in |G*| with acid addition to Pembina and an overall decrease in |G*| when using Harvest. Conclusions: The effect of cultivar, salt content and acid type was highly interdependent for the dough complex modulus, tan δ, maximum creep compliance, and relative elasticity along with dough stickiness. Significance and novelty: This research provides fundamental knowledge on the effect of salt reduction and acidulants on dough rheology with a view to understanding how water incorporation in the gluten network affects attempts to reduce sodium content in the dough without impairing dough handling properties.